Patronage, tradition and modernisation - case of Irish gombeenman - Gibbon, Peter; Higgins, M.D. (Economic & Social Studies, 1974)
As part of a general movement toward the study of complex societies in political anthropology, the last few years has witnessed a proliferation of empirical studies in patron-client ties. Most of this literature has been essentially descriptive in character, but more recently attempts have been made to analyse the problem of the relation between transitions in these ties and the kinds of structural change implied by the notion of increasing social 'complexity' .
Keywords: Patron-Client ties; Patronage - Ireland